EKSPRESI TINDAK DIREKTIF DALAM INTERAKSI KELAS BENGKEL JURUSAN TEKNIK MESIN POLITEKNIK NEGERI MALANG - Moh Thamrin (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2010)
This study was a qualitative study employing the pragmatic approach. Thesubjects comprised the lecturer and students of the workshop class in the Department of Mechanical Engineering of the State Polytechnic of Malang. The data were ollected through observations. The researcher was the key instrument, equipped with observation guides and an electronic recorder. The data were analyzed using the interactive analysis model by Miles and Huberman in three steps: (1) data reduction, (2) data display, and (3) conclusion drawing or verification. The results show that lecturer-student directive acts in the workshop class interaction are dominated byimperative sentences more than declarative and interrogative sentences. Studentlecturer directive acts are dominated by interrogative sentences. The functions of lecturer-student directive acts are more varied than those of student-lecturer directive acts. The request function in the lecturer-student interaction is the most dominant function among other functions. In the student-lecturer interaction, the command function is more dominant than the request function.